Developing And Validating Middle School Mathematics Teachers’ Pedagogical Competency Scale - Aggarwal, Aarti; Dahiya, Jyoti; Raghu, Ananthula (Journal of Neonatal Surgery, 2025)
This study aims to design, develop, and validate a comprehensive measuring tool to assess the pedagogical competencies of middle school mathematics teachers. Acknowledging the important role of mathematics education in promoting cognitive development, critical thinking, problem-solving skills, and logical reasoning, this study examines the need for effective teaching methods during the significant middle school years (grades 6 to 8) and therefore, the need for a standardized assessment tool. The research followed a structured process for developing the tool including a comprehensive literature review and insights from experts, followed by item generation, pilot testing, and thorough statistical validation. The first draft of the Mathematics Teachers’ Pedagogical Competency Scale (MTPCS) consisted of 90 items, which were adjusted to 80 items after expert review. These items were classified into eight key dimensions of pedagogical competency: (1) Conceptual Understanding and Core Knowledge, (2) Different Teaching Methods and Multidisciplinary Approach, (3) Understanding Different Types of Learners, (4) Mathematics Assessment, (5) Use of Teaching-Learning Resources, (6) Use of Technology, (7) Growth Mindset, and (8) Classroom Management. A total sample of 186 mathematics teachers from different schools in Delhi took part in the pilot testing of the tool. Item analysis was done with the help of t-values, which detected and removed items with weak discriminatory power, leading to a final tool consisting of 55 items. The tool was found to be highly reliable (Cronbach’s Alpha = 0.94) and valid, establishing it as a robust instrument to measure the teachers’ pedagogical competencies. This research adds to the domain of teacher education by providing a standardized tool for assessing and enhancing the teaching practices of middle school mathematics teachers.